What Makes Capital Account Regulation Effective? Comparing the Experiences of Brazil, Peru, and Iceland. Issue 3 (2nd July 2020) - Aguirre, Pablo; Alonso, José Antonio
Abstract : Empirical studies confirm that the impact of capital account regulation (CAR) is highly case-specific, which underlines the need to identify the determinants of CAR effectiveness in greater depth. Coming from a political economy perspective, this article aims to contribute to this subject by comparing three experiences of intense regulation: Brazil (2008-2013), Peru (2008-2013), and Iceland (2008-2017). The main result encountered is that the bargaining power of the different sectors involved in regulation represents a crucial factor in explaining the impact of this policy. Furthermore, domestic banks play an important role in the effectiveness of capital account regulation.